Critical Study on Bekerja Program Implementation as Economic Empowerment: Sharia Economic Perspective - H, Muh Ilyas; Idris, Mahsyar; Semaun, Syahriyah; Ali, St Nurhayati; Damirah, Damirah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The research aims to assess BEKERJA program's effectiveness in reducing poverty in Salutambung Village by providing farm animals. It evaluates the program's impact on economic empowerment, food security, and its alignment with Islamic economic principles, while addressing challenges like resource misallocation and dependency. The research methodology involves qualitative analysis to evaluate the program's impact in Salutambung Village through interviews and observations as field research. Data collection includes examining economic empowerment, food security, collaboration with Social Affairs Department, and alignment with Islamic economic principles. The study concludes that the BEKERJA program effectively reduces poverty by providing livestock to needy households, enhancing economic empowerment and food security. The program's collaboration with the Social Affairs Department has improved community welfare and economic conditions. However, some social assistance programs, including BEKERJA, face challenges such as resource misallocation and lack of technical support. The research lacks analysis that could contribute to further improving BEKERJA program